2013
DOI: 10.1212/wnl.0b013e31828cf8a2
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes 6 virus encephalitis complicating allogeneic hematopoietic stem cell transplantation

Abstract: Objective: To describe the presentation and management of encephalitis due to human herpes 6 virus (HHV-6) in patients who underwent allogeneic hematopoietic stem cell transplant (alloHSCT), via retrospective chart review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 12 publications
4
76
2
1
Order By: Relevance
“…3,7,[36][37][38]41,42 Some investigators have termed this finding 'post-transplant acute limbic encephalitis (PALE) 38,40,[42][43][44] and HHV-6 PALE has been diagnosed when the patient has detectable HHV-6 DNA in cerebrospinal fluid in the context of acute-onset altered mental status, amnesia, seizures or other evidence of medial temporal lobe disease involving the limbic system and no other identifiable etiology. 38,42 A recent retrospective study 45 showed, however, not all cases of HHV-6-associated CNS dysfunction meet the criteria for PALE. HHV-6 may also cause myelitis that presents with systemic pruritus and severe pain in the extremities.…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
See 2 more Smart Citations
“…3,7,[36][37][38]41,42 Some investigators have termed this finding 'post-transplant acute limbic encephalitis (PALE) 38,40,[42][43][44] and HHV-6 PALE has been diagnosed when the patient has detectable HHV-6 DNA in cerebrospinal fluid in the context of acute-onset altered mental status, amnesia, seizures or other evidence of medial temporal lobe disease involving the limbic system and no other identifiable etiology. 38,42 A recent retrospective study 45 showed, however, not all cases of HHV-6-associated CNS dysfunction meet the criteria for PALE. HHV-6 may also cause myelitis that presents with systemic pruritus and severe pain in the extremities.…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
“…[50][51][52][53] Criteria frequently used in the literature to define HHV-6 encephalitis include: the presence of neurological symptoms (altered mental status, altered level of consciousness, amnesia, seizures and change in personality and behavior); positive PCR results for HHV-6 in cerebrospinal fluid (ciHHV-6 should be excluded); and the absence of other identified etiologies of CNS dysfunction. 5,15,37,44,45,54 This criterion may enable physicians to diagnose HHV-6 encephalitis effectively and efficiently. False-positive results for HHV-6 DNA in cerebrospinal fluid may occur, 50,52,55 and hence positive results must be interpreted carefully in conjunction with clinical symptoms and negative results for other etiologies.…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this disease generally manifests as a benign self-limiting febrile illness (2), in rare cases it can cause severe complications, including encephalitis (3,4) and fulminant hepatitis (5). HHV-6B reactivation has clinical manifestations in transplant recipients, such as skin rash and fever (6,7) and bone marrow suppression and posttransplant acute limbic encephalitis (8)(9)(10)(11)(12)(13). Antiviral drugs, such as ganciclovir (GCV) and foscarnet, have been used to treat transplant recipients with HHV-6B-associated encephalitis (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The antiviral effect of GCV against HHV-6B has been demonstrated using in vitro susceptibility assays (17)(18)(19). The in vivo efficacy of GCV remains inconclusive, despite its general use in patients with HHV-6 encephalitis posttransplantation (8)(9)(10)(11)(12)(13). The U69 gene in HHV-6 is a homologue of the HCMV UL97 gene, and it phosphorylates GCV (20,21).…”
mentioning
confidence: 99%